Service-learning pedagogy : how does it measure up? - Jagla, Virginia M., 1948-; Furco, Andrew; Strait, Jean, 1965- (Advances in service-learning research., 2015)
Service-learning is a powerful method of teaching and learning that has been used effectively for more than two decades. Its efficacy has been researched in a variety of ways and this volume continues to expand that research base. In particular, in this volume, Service-Learning Pedagogy: How Does It Measure Up?, we explore three broad areas of service-learning research and practice that reflect broader discussions of the role of pedagogy in today's educational reform efforts: Teacher Education, Crossing Boundaries: Deepening Relationships in Service-Learning and New Paradigms/Conceptual Frameworks.Many have called for more rigorous methods when researching service-learning pedagogy. That has been the major impetus for this volume. We seek to generate knowledge regarding service-learning pedagogy, while developing theories about it. We surface some elusive affective characteristics of the pedagogy, which we know has the power to produce transformational learning. To this end, the authors who have contributed to this volume effectively add to the growing body of knowledge in the field and help us get closer to understanding the extent to which service-learning does and does not measure up.